A importância da mucosa queratinizada na implantodontia - Novaes, Vivian Cristina Noronha [UNESP]; Santos, Murillo Rezende [UNESP]; Almeida, Juliano Milanezi de [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Mendonça, Marcos Rogério de [UNESP] (My University, 2012)
The purpose of current implantology is to ensure that implants maintain its state of full health, proper function and aesthetics. The aim of this paper is to discuss, through a literature review, the importance of keratinized mucosa in relation to cleaning, gingival maintenance, aesthetics involving dentistry implant and evaluating some options to provide a keratinized mucosa when it is insufficient. For the studies identification, it is included or considered in this review, Pubmed database with the following keywords: implant and mouth mucosa and, according to the criteria for inclusion and exclusion, 27 articles were selected. According to the reviewed articles, it was found that the keratinized tissue does not influence the survival of the implant, but it facilitates the cleaning, decreases the irritation of the peri-implant tissues and promotes aesthetics in anterior regions.

A proposta da implantodontia atual é garantir que os implantes, além de osseintegrados, mantenham seu estado de plena saúde, função e estética adequada. O objetivo deste artigo é discutir, por meio de uma revisão de literatura, a importância da mucosa queratinizada com relação à higienização, a manutenção gengival e a estética envolvendo a implantodontia, bem como avaliar algumas opções para proporcionar uma quantidade de mucosa queratinizada quando esta é insuficiente. Para a identificação dos estudos incluídos ou considerados nesta revisão, foi utilizado o banco de dados Pubmed com os descritores: implant e mouth mucosa e, seguindo com os critérios de inclusão e exclusão, foram selecionados 27 artigos. De acordo com os artigos revisados considerou-se que o tecido queratinizado não influencia diretamente na sobrevida do implante; porém ele facilita a higienização, diminue a irritação dos tecidos periimplantares e favorece a estética em regiões anteriores.
Importance of keratinized mucosa in implantology
Keywords: Implant; Mouth mucosa; Implante; Mucosa buca